Retinal Nerve Fibre Layer Thickness Change Following Femtosecond Laser-Assisted in situ Keratomileusis - Jiang, Yang; Wang, Zhonghai; Li, Ying; Li, Yong; Lu, Thomas Chengxuan (Frontiers in Medicine, 2021)
PURPOSE: To evaluate the effect of femtosecond laser-assisted in situ keratomileusis (FS-LASIK) on retinal fovea thickness, volume and retinal nerve fibre layer (RNFL) thickness. METHODS: Thirty-seven eyes (37 patients) undergoing FS-LASIK were included this prospective study. Optical coherence tomography (OCT) were performed 1 day before, 1 hour and 1 day after FS-LASIK surgery. Comparison were made for retinal fovea (macula fovea, parafovea and perifovea) thickness and volume pre-and post FS-LASIKS. Similarly, RNFL (temporal, superior, nasal and inferior) thickness pre-and post FS-LASIK were compared. Paired T-test was utilised to determine statistical significance. RESULTS: Eighteen male and nineteen females were enrolled. Mean patient age was 22.94±4.22 years. Mean macula fovea thicknesses were 67.18±10.25µm, 57.81±10.5µm and 62.24±10.64µm before, 1 hour and 1 day after FS-LASIK surgery(t=6.171, p=0.000;t=3.620, p=0.001). Mean macula fovea volume were 0.527±0.081mm2, 0.454±0.082mm2 and 0.495±0.088mm2 before, 1 hour and 1 day after FS-LASIK surgery(t=6.032, p=0.000;t=3.220, p=0.003).Mean macula parafovea thickness were 124.29±7.61µm, 100.43±15.98µm and 120.18±8.33µm before, 1 hour and 1 day after FS-LASIK surgery(t=9.837, p=0.000;t=2.901, p=0.006). Mean macula parafovea volume were 0.780±0.047mm2, 0.634±0.098mm2 and 0.755±0.052mm2 before, 1 hour and 1 day after FS-LASIK surgery(t=9.700, p=0.000;t=2.910, p=0.006).Mean macula perifovea thickness were 98.83±2.57µm, 91.81±1.48µm and 100.75±4.41µm before, 1 hour and 1 day after FS-LASIK surgery(t=2.532 p=0.016;t=0.694, p=0.492). Mean macula perifovea volume were 2.128±0.199mm2, 1.941±0.183mm2 and 2.107±0.187mm2 before, 1 hour and 1 day after FS-LASIK surgery(t=4.393,p=0.000;t=0.525, p=0.603). Mean tempotal RNFL thickness were 98.08±10.14µm, 86.86±13.56µm and 99.59±12.4µm before, 1 hour and 1 day after FS-LASIK surgery(t=4.926,p=0.000;t=0.905, p=0.372). Mean superior RNFL thickness were 129.24±12.79µm, 123.97±17.16µm and 126.78±14.69µm before, 1 hour and 1 day after FS-LASIK surgery(t=2.265,p=0.011;t=1.166, p=0.251). Mean nasal RNFL thickness were 58.00±9.08µm, 58.67±11.52µm and 59.51±9.98µm before, 1 hour and 1 day after FS-LASIK surgery(t=0.443,p=0.66;t=1.727, p=0.093). Mean inferior RNFL thickness were 124.29±13.56µm, 122.05±17.42µm and 129.24±14.17µm 1 day before, 1 hour and 1 day after FS-LASIK surgery(t=0.997,p=0.325;t=3.632, p=0.001). CONCLUSIONS: Our data suggests there are alterations in retinal foveal and RNFL measurements by OCT 1 hour and 1 day after FS-LASIK surgery.